Chapter 2: If you can’t be secure, be resilient - Wilkinson, Edith; Cleary, Laura R. (Routledge, 2021)
This chapter offers a commentary on the way in which the concepts of resilience and security have evolved and amalgamated over time. Beyond consideration of the evolution of the respective concepts, the chapter examines how risk-based approaches underpin today’s implementation of resilience. Although the idea of adaptation features prominently in the understanding of resilience, it appears to be limited in the context of risk management. This brings the authors to consider a layered approach to living with risk and uncertainty. A conceptual framework is put forward for the resilience of security institutions, thereby contributing to national resilience. The proposed model places a novel emphasis on institutional and political cultures; the aim being to embrace whole-of-society approaches to security.